Inflammatory Cytokines and BDNF Response to High-Intensity Intermittent Exercise: Effect the Exercise Volume - Cabral-Santos, Carolina [UNESP]; Castrillon, Carlos I. M. [UNESP]; Miranda, Rodolfo A. T. [UNESP]; Monteiro, Paula A. [UNESP]; Inoue, Daniela S. [UNESP]; Campos, Eduardo Z. [UNESP]; Hofmann, Peter; Lira, Fabio S. [UNESP] (Frontiers Media Sa, 2016)
The purpose of this study was to compare the effects of two similar high-intensity intermittent exercises (HIIE) but different volume 1.25 km (HIIE1.25) and 2.5 km (HIIE2.5) on inflammatory and BDNF responses. Ten physically active male subjects (age 25.22 +/- 1.74 years, body mass 78.98 +/- 7.31 kg, height 1.78 +/- 0.06 m, VO2peak 59.94 9.38 ml-kg-min(-1)) performed an incremental treadmill exercise test and randomly completed two sessions of HIIE on a treadmill (1:1 min at vVO(2max) with passive recovery). Blood samples were collected at rest, immediately and 60-min after the exercise sessions. Serum was analyzed for glucose, lactate, IL-6, IL-10, and BDNF levels. Blood lactate concentrations was higher immediately post-exercise compared to rest (HIIE1.25: 1.69 0.26-7.78 +/- 2.09 mmol-L-1, and HIIE2.5: 1.89 +/- 0.26-7.38 +/- 2.57 mmol-L-1, p < 0.0001). Glucose concentrations did not present changes under the different conditions, however, levels were higher 60-min post-exercise than at rest only in the HIIE1.25 condition (rest: 76.80 +/- 11.14-97.84 +/- 24.87 mg-dL(-1), p < 0.05). BDNF level increased immediately after exercise in both protocols (HIIE1.25: 9.71 +/- 306-17.86 +/- 8.59 ng.mL(-1), and HIIE2.5: 11.83 +/- 5.82-22.84 +/- 10.30 ng.mL-1). Although both exercises increased IL-6, level percent between rest and immediately after exercise was higher in the HIIE2.5 than HIIE1.25 (30 and 10%; p = 0.014, respectively). Moreover, IL-10 levels percent increase between immediately and 60-min post exercise was higher in HIIE2.5 than HIIE1.25 (37 and 10%; p = 0.012, respectively). In conclusion, both HIIE protocols with the same intensity were effective to increase BDNF and IL-6 levels immediately after exercise while only IL-10 response was related to the durantion of exercise indicanting the importance of this exercise prescription variable.
Keywords: high-intensity intermittent exercise; inflammatory response; metabolic response; cytokines; low-grade inflammation